WHIP SANCTIONS IN THE CRIMINAL ACT OF PROSTITUTION BASED ON QONUN ACEH NUMBER 06 OF 2014 CONCERNING JINAYAT LAW FROM A HUMAN RIGHTS PERSPECTIVE - Faisol Dzikir Towil; Abdul Rokhim; Diyan Isnaeni (Pena Cendekia Insani, 2025)
This study focuses on the application of caning sanctions in criminal law in Aceh, especially in cases of prostitution, by examining the historical, legal, and cultural dimensions as the basis for the legitimacy of the punishment. The research method used is qualitative with a case study approach, including legal document analysis, in-depth interviews, and field observations to obtain comprehensive empirical data. The results of the study indicate that caning punishment is not merely a product of formal law, but also a symbol of social and moral control that is strongly legitimized by religious traditions and local cultural norms. The implications of this study emphasize the need for a multidimensional understanding in enforcing sharia law in order to adapt to the principles of human rights and the ever-evolving social dynamics of Acehnese society.